FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK APPLE IPHONE - Ratih, Faradika Maria; Mulyati, Awin; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2016)
Researcher did a research related to "Factors affected consumers' decision in buying iPhone Apple product". According to Kotler (2005; 203) behavior of consumers in buying is affected by 4 factors namely custom factor(x1), social factor (x2), personal factor(x3), and psychologycal factor(x4). Due to those factors, the researcher wanted to know how far effects of the four factors to buying decision of apple iphone. Results of the research obtained from 100 respondents (Surabaya citizens) who are consumers of Apple iPhone and processed using SPSS for windows 17.0.The results of the research showed that correlation test explained that there was significant effects between custom, social, personal, and psychologycal factor and the buying decision of Apple iPhone. From the four factors, psychologycal factor was the most dominant factor which affected the buying decision of Apple iPhone. To gain the buying decision, produsers should concern on custom, social, personal, and psychologycal factor of Apple iPhone consumers. Keywords: Buying decision, customer, social, personal, psychologycal factors